Slovenia : Pilot Diagnostic Review of Governance of the Insurance Sector - World Bank (Washington, DC, 2013)
This review looks at the governance of the insurance sector in Slovenia, analyzing the legal framework and its enforcement and the adoption of corporate governance principles by firms. It is intended to provide policy makers and insurers in Slovenia, and other countries, with insight into existing corporate practices, and to offer a framework of good practices that can assist lawmakers in their efforts to strengthen governance in the insurance sector. The report may also contribute to the ongoing international debate on good corporate governance practices in insurance sector companies worldwide. It has three objectives: improving the description of good practices related to governance of insurance sectors; conducting a diagnostic review of Slovenian insurance governance against these benchmarks, and providing recommendations on ways of further improving the corporate governance of the Slovenian insurance sector. The review concludes with recommendations for auditing and risk evaluation, and advises that, although Slovenia's three finance regulators have served it well to date, the regulatory and supervisory structure for the finance sector is in need of more review before a joint working group could be established to implement the legal, organizational, media, and sequencing issues involved in creating an integrated regulatory agency.